Saccharomyces cerevisiae Fermentation Products That Mitigate Foodborne Salmonella in Cattle and Poultry - Feye, Kristina M.; Carroll, Jasmine P.; Anderson, Kristi L.; Whittaker, John H.; Schmidt-McCormack, Garrett R.; McIntyre, Don R.; Pavlidis, Hilary O.; Carlson, Steve A. (Frontiers in Veterinary Science, 2019)
Prior studies revealed that yeast fermentation products, specifically XPCTM and related products (Diamond V, Cedar Rapids, IA), serve as viable food safety tools across multiple food animal species including cattle and poultry. Providing this supplement in feed leads to reduced prevalence, load, virulence, and antibiotic resistance of foodborne pathogens such as Salmonella and Escherichia coli O157:H7. These findings are worthy of further study, especially when coupled with the enhanced growth and performance observed with these products. Mechanistically, XPC appears to modulate these effects through the immune system and gut microbiome. Herein we further investigated this product and demonstrate that XPC mediates an enhancement of immunocyte killing of Salmonella in calves fed the product. Additionally, these studies reveal that XPC reduces the lymph node infiltration, invasiveness, and antibiotic resistance of Salmonella in dairy calves fed the product- consistent with findings observed in poultry and adult beef cattle. Furthermore, the reduction in invasiveness does not lead to a rebound hyperinvasive phenotype in Salmonella obtained from XPC-fed animals.